Green Innovation for Small-to Medium-Sized Enterprises (SMEs): Systematic Literature Review - Mediaty; Diza Kurnianty Jamal; Abdul Hamid Habbe (Indonesian Journal of Economic & Management Sciences, 2023)
The green innovation literature of the past few decades is not only interesting for research due to its high level of environmental awareness and the provision of green products and services, but also because of its widespread and important applications. This study aims to determine research trends related to the adoption of green innovation, especially in SMEs during 2013-2023 by using Systematic Literature Review techniques. The result of this research identifies the key elements factors of GI for managers and ultimately serve as an important reference to help formulate GI activity strategies. This research can serve as a foundation for scientific development so that the number of studies related to new topics related to green innovation also continues to increase